(untitled) (Fiep Bulletin - online, 2014)
The aim of the article is to present a partial report on data collected and analyzed at the Nova Geração (New Generation) football school. The object here is to show how the transmission of physical skills occurs in the process of teaching and learning of football, and the motivations of the youngsters to participate in the Nova Geração football school, run by an untrained professional.The method used was direct observation of the classes, with the use of field diaries, and from interviews and questionnaires conducted with the students. We observed classes in the following age categories: Mirim, Infantil, Juvenil e Juniores.The observations made in the period in which we attended classes at the Nova Geração football school show that the ’collective game’ is the principal strategy used by the teacher to teach football.The forms of coercion imposed during the classes, by way of punitive measures, reinforce what the teacher deems necessary for his students to learn in order to improve their performance in the game. The concepts ’objectivity’ and ’collective game’ can be observed in a striking manner in the discourse.The dream of moving upward in society via football is a reality and a powerful influence on the boys’ attendance of the project.